Predisposing Factors of Cardiovascular Events among COVID-19 Patients - Devina Gabriella Nugroho; Putri Rachmawati Dewi; Rima Adjani Nugroho; Santoso Jaeri (Faculty of Medicine Universitas Kristen Duta Wacana, 2022)
Background COVID-19 is an infectious respiratory disease caused by SARS-CoV-2. During hospitalization, there is the possibility of cardiovascular events. The presence of these events might be related to some factors, unfortunately, there is limited evidence for these issues.Objective The aim of the study was to determine the independent predisposing factors associated with the occurrence of the cardiovascular event among COVID-19 patients during hospitalization.Method A retrospective study using medical records of hospitalized COVID-19 patients in K.R.M.T Wongsonegoro Hospital Semarang Indonesia, periods of June to September 2020. One hundred and one patients were included in the study. The subjects were classified into CVE groups and non-CVE, then the demographic characteristics and clinical data were collected. The Chi-Square, the Independent-T as well Mann-Whitney U test were used. The logistic regression then was used to determine the odds ratio of predisposing factors for CVE occurrence.Results There were significant associations for the history of cardiovascular disease, smoking, hypertension, use of angiotensin-converting enzyme inhibitor agents, the level of blood glucose and troponin I, and the systolic blood pressure at the first visit for CVE occurrence. Furthermore, the history of CVD increased the risk 0,007 times to get CVE.test.Conclusion The history of cardiovascular disease, smoking, hypertension, use of angiotensin-converting enzyme inhibitor agents, the level of blood glucose and troponin I, and the systolic blood pressure at first visit are the predisposing factors for the development of CVE among COVID-19 patients and patient who has the history of CVD have a high risk to get CVE during hospitalization.